A Scoping Review of Epilepsy Care in Low-Resource Settings: Addressing Stigma, Healthcare Disparities, and Socioeconomic Barriers - Willie, Michael Mncedisi (Journal of Indonesian Health Policy and Administration, 2025)
Epilepsy affects around fifty million people worldwide, with stigma and limited healthcare access posing significant challenges, especially in low-resource settings. This scoping review aimed to identify key barriers to epilepsy care, focusing on stigma, healthcare access, and socioeconomic factors in sub-Saharan Africa and similar contexts. Using the Arksey and O’Malley framework, a systematic search was conducted across online databases for peer-reviewed studies published. The review found that stigma significantly delayed diagnosis, increased social isolation, and reduced treatment adherence. Healthcare barriers included a lack of trained professionals and inadequate treatment protocols. Socioeconomic challenges, such as poverty and rural residency, were linked to lower healthcare utilisation and medication non-adherence. Additionally, limited public awareness reinforced misinformation and discrimination. The findings highlight the urgent need for targeted health interventions, public education, and stronger integration of epilepsy care into primary healthcare, particularly in underserved regions.